Analysis of Affecting Variables Actual Inflation Rate at Indonesia - Andy Chandra; Kemal Taufik; Cicih Ratnasih (CV. Publikasi Indonesia, 2024)
The discussion in this empirical study is to find out what variables can influence the achievement of the actual inflation rate variable in Indonesia in the last ten years. The writer considers that achieving the actual inflation rate targeted by a Central Bank is not simply related to supply and demand imbalances for primary goods alone, but more broadly than that related to dynamic micro and macroeconomic conditions. The writer initially suspected that variables such as the inflation target rate, previous inflation rate, loan interest rate, and gross domestic product had a significant influence on fluctuations in the actual inflation rate in Indonesia. After statistical tests were carried out using the secondary data in the form of the rates of the four independent variables and the actual inflation rate in Indonesia as the dependent variable every year for the last ten years it’s found that only the loan interest rate had a significant and positive effect on the actual inflation rate in Indonesia. which means that the higher the loan interest rate will also increase the actual inflation rate. The three other variables tested in this empirical study, namely the inflation target rate, the previous inflation rate, and the gross domestic product rate, did not have a significant effect.